TRANSFORMATION OF THE UKRAINE’S INDUSTRIAL SECTOR IN CONDITIONS OF OVERCOMING DEINDUSTRIALIZATION - Lyubov H. Kvasniі; Anna V. Voloshanska (Academy Review)
The article demonstrates that deindustrialization, which has occurred in Ukraine in recent years, hinders stable and long-term growth. In this context, the theoretical and methodological impact of deindustrialization processes on Ukraine’s economy amid the financial crisis is examined, and proposals for an innovative development model for Ukraine’s recovery from the crisis are outlined. The necessity of forming and implementing a new industrial policy within modernization processes is highlighted, emphasizing the critical role of industry in addressing current issues through a suitable model of industrialization. Key guidelines for the development of Ukraine’s domestic economy are argued, focusing on rational growth, sustainable and inclusive development as means to counter deindustrialization and transition to the sixth technological paradigm. The article establishes the purpose of studying the impact of deindustrialization on Ukraine’s economy and developing strategies for transforming its industrial sector within an innovative framework. It is concluded that only a diversified, high-tech industrial base, particularly in manufacturing, can ensure economic growth in Ukraine. It is substantiated that Ukraine has adopted an inverse industrial development model, characterized by export and raw material orientation, which is closely linked to the country’s deindustrialization process. Through analysis of scientific literature and original research using scientific methods, the article outlines priority areas for Ukraine’s industrial development: energy engineering, transport, aerospace engineering, equipment production for alternative energy (including new materials and energy storage), weapons and special equipment manufacturing, and information and communication technologies. The primary findings, theoretical positions, conclusions, and practical recommendations from this study can inform strategic directions for Ukraine’s industrial sector and overall economic development, drawing on the experience of developed countries and considering current post-industrial trends and their impact on regional potential. Future research may focus on developing further scenarios for regional development based on region type and its innovation potential.